P-16=13-6p

Simple and best practice solution for P-16=13-6p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for P-16=13-6p equation:


Simplifying
P + -16 = 13 + -6p

Reorder the terms:
-16 + P = 13 + -6p

Solving
-16 + P = 13 + -6p

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + P = 13 + 16 + -6p

Combine like terms: -16 + 16 = 0
0 + P = 13 + 16 + -6p
P = 13 + 16 + -6p

Combine like terms: 13 + 16 = 29
P = 29 + -6p

Simplifying
P = 29 + -6p

See similar equations:

| 4c+1-c=19 | | (x+5)(x-2)=35 | | 8b-5b-7=23 | | 8y+4y=144 | | 2.5[x+3(x+7)]= | | 6x+8y=-11 | | (3a)+(2a-25)=180 | | .50(x-2)=4x-0.2222x-4 | | 5(3b-4)=40 | | 3(4x+3)=17 | | 6r+5=4(r+2)-2r | | 2yf-3(2y-3)+2=31 | | F(x)=x^3+2x^2+x+4 | | 2n-1=-10 | | 11=4(x-1)-x | | 2600=(2x-6)m+(x+3)m | | 4x+5=16x+8-12x-3 | | 1.8x+2.8=2.5*2.1 | | -108=3(4+8n) | | 2[4x+1]+5=19 | | (8x-12)(5x-25)=0 | | (a)3.43x=5.6 | | 2[4x+1]5=19 | | 7(y-3)=4y-33 | | 25=3+9x | | 2+.142x=9 | | 3b-2=14 | | 2a-7=4(3a+1)-2 | | -6x-x+10=16-7x-5 | | 3x-5(x-5)=-7+4x-16 | | (-3)(-2)+(-2)(4)= | | 12+5x=-2x-11 |

Equations solver categories